Aerosol dynamics model for the simulation of hygroscopic growth and deposition of inhaled NaCl particles in the human respiratory tract. (November 2017) - Winkler-Heil, Renate; Pichelstorfer, Lukas; Hofmann, Werner
Abstract: The purpose of the present work is the implementation of the aerosol dynamics model ADiC, specifically its heat/vapor transport and phase transition components, into the stochastic lung deposition model IDEAL. The combined ADiC/IDEAL model allows the simultaneous calculation of relative humidity, hygroscopic growth and deposition of inhaled NaCl aerosols in individual airways of the human lung along randomly selected particle paths and randomly selected times during the inhalation phase. Hygroscopic growth decreases deposition of submicron particles compared to hydrophobic particles with equivalent diameters due to a less efficient diffusion mechanism, while the more efficient impaction and sedimentation mechanisms increase total deposition for micrometer particles. Due to the variability and asymmetry of the human airway system, individual trajectories of inhaled particles are associated with individual growth factors. For a realistic breathing scenario, particles are inhaled at different times during the inspiratory phase and hence experience individual growth factors, thereby further enhancing the variability of individual growth factors and resulting deposition patterns. While nanometer particles adopt their equilibrium growth factor value already within the mouth and pharynx/larynx during the inspiratory phase, micrometer particles approach this value at the end of inspiration, thus further increasing in size during the exhalation phase. In summary, individual hygroscopic growth factors vary for different paths and different inhalation times. For model validation purposes, theoretical predictions were compared with human experimental deposition data and previous hygroscopic growth model simulations for total deposition of ultrafine and micrometer-sized NaCl particles. Highlights: Implementation of an aerosol dynamics model into a stochastic lung deposition model. Simultaneous calculation of relative humidity, hygroscopic growth and deposition. NaCl hygroscopic growth factors vary for different paths and inhalation times. Model validation by comparison of model predictions with human NaCl deposition data. Further development of a general aerosol dynamics model for inhalation.